The Pula Batèe Ritual on Death Ceremonies in Lam Ilie Teungoh Society Indrapuri District-Aceh Besar - Ibrahim, Arfah; Manan, Abdul; Farijal (Indonesian Journal of Islamic History and Culture, 2025)
The pula batèe ritual which has taken root in society is one of the traditions in death ceremonies. This research was conducted in Lam Ilie Teungoh village, Indrapuri District, Aceh Besar. The aim of this research is to determine the process of carrying out the pula batèe ritual, the symbolic meaning contained in the pula batèe ritual, as well as the teungku's response to the pula batèe ritual. This research uses qualitative methods with data collection instruments in the form of observation, interviews, and documentation. The data were analyzed by means of data reduction, data presentation, and drawing conclusions. The findings show that the pula batèe rituals are carried out by the teungku imum by reading prayers that bring goodness to the corpse. The pula batèe ritual is performed on the seventh day after death. The meaning is that the stone used can always glorify the corpse and the jarak tree (bak nawah) used can shed away sins and the coconut leaves are used so that the corpse will always be in the ranks of the faithful. Teungku's views of the pula batèe ritual at death ceremonies are positive because the pula batèe ritual does not conflict with Islam and in practice contains religious values ​​and generates solidarity between people in society.